The Relationship between Financial Risk and Financial Sustainability of State-Owned Asset Management Companies in Thailand - Tangdoungthip, Ittikorn; Chatakanonda, Sophanat (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research on the relationship between financial risk and financial sustainability of state-owned asset management companies in Thailand has three main objectives: 1) to study the overview and competitive environment in the debt management industry for major state-owned asset management companies; 2) to explain and compare the trends of financial risk and sustainability indicators; and 3) to propose suitable debt management guidelines to promote their financial sustainability. The research findings indicate that: 1) The asset management industry has seen increased competition since 1997 due to the entry of new competitors and price competition in the auction of non-performing assets. However, State-Owned Asset Management Companies (SOAMCs) still maintain advantages in expertise, networks, and valuation capabilities. SOAMCs receive government support, which provides a capital advantage and a monopoly on purchasing large debts from state financial institutions. Meanwhile, private companies primarily focus on the retail market. 2) The slow economic recovery and rising household debt have reduced debtors’ ability to repay, making the sale of Non-Performing Assets (NPAs) more difficult. For BAM and IAM, which have similar financial data, it was found that both companies experienced asset growth, but their profitability has declined. The net profit margin decreased from 21.32% in 2022 to 12.53% in 2024. ROA and ROE also show a downward trend. Market risk is reflected in their stock prices, with a decline in market prices indicating a lack of investor confidence. Regarding SAM, the company experienced consecutive net losses for three years from 2022 to 2024. This resulted in a decrease in shareholders’ equity and book value per share. All profitability ratios (ROA, ROE, net profit margin) were negative. Its market value also decreased, with the stock price falling from 1.18 THB in 2021 to 0.20 THB in 2024. 3) Recommended debt management guidelines to build financial sustainability include enhanced operational efficiency, risk management, and structural improvements. Article history: Received 12 May 2025 Revised 7 November 2025 Accepted 9 November 2025 SIMILARITY INDEX = 4.49 %